A method for energy efficiency assessment during urban energy planning. Issue 2 (9th September 2014) - Regina de Casas Castro Marins, Karin
Abstract : Purpose: – Energy use in urban areas has turned a subject of local and worldwide interest over the last few years, especially emphasized by the correlated greenhouse gases emissions. The purpose of this paper is to analyse the overall energy efficiency potential and emissions resulting from integrated solutions in urban energy planning, in the scale of districts and neighbourhoods in Brazil. Design/methodology/approach: – The approach is based on the description and the application of a method to analyse energy performance of urban areas and support their planning. It is a quantitative bottom-up method and involves urban morphology, urban mobility, buildings and energy supply systems. Procedures are applied to the case study of Agua Branca urban development area, located in Sao Paulo, Brazil. Findings: – In the case of Agua Branca area, energy efficiency measures in buildings have shown to be very important mostly for the buildings economies themselves. For the area as a whole, strategies in promoting public transport are more effective in terms of energy efficiency and also to decrease pollutant emissions. Originality/value: – Literature review has shown there is a lack of approaches and procedures able to support urban energy planning at a community scale. The bottom-up method presented in this paper integrates a plenty of disaggregated and multisectoral parameters at the same stage in urban planning and shows that is possible to identify the most promising actions by building overall performance indexes.